Znaczenie badań historycznojęzykowych dla interpretacji zjawisk współczesnej polszczyzny - Siuciak, Mirosława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The article contributes to the discussion on the interpretation of processes taking place in the contemporary Polish language from two perspectives: diachronic and synchronic (ahistorical, to be precise). The author draws attention to the problem of not accounting for the achievements of diachronic linguistics, which is visible in the studies devoted to the analysis of the language used by the contemporary Poles. This leads to a situation in which the same research questions are not infrequently examined and interpreted in completely different ways in synchronic studies and those dealing with the history of language. Sometimes the differences are so vast that coherent scientific discourse becomes disabled. Enriching the investigation of the processes occurring in the contemporary Polish language with conclusions drawn from analysing historical sources is thus an important claim. Considering the diachronic perspective could be particularly beneficial for discussing the issue of the norm. Since a number of problems with language correctness result from tendencies and processes which have been happening in language for centuries, only becoming acutely aware of them can bring a change in understanding codification and the linguistic norm.